Tuanar-esoh Tohsoh: Enhancing English-Speaking Skills with TikTok Application for Cooperative Education Preparation in the Faculty of Liberal Arts, Princess of Naradhiwas University - Tohsoh, Tuanar-esoh; Laseng, Suhaida; Ngoh, Anis; Yapa, Aidah; Kamhaengkit, Rojarek (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2024)
DOI: 10.14456/pnuhuso.2024.5 This study aimed to 1) compare students’ English-speaking skills before and after the implementation of learning activities through the TikTok application, and 2) determine students’ satisfaction with the English-speaking learning activities utilized in their preparation for the cooperative education program. The sample group for this study comprises English majors in their third academic year within the Faculty of Liberal Arts in 2022, selected through the application of simple random sampling. The research tools included: 1) English-speaking learning activities for the preparation of cooperative education; 2) the cooperative education English-speaking skills assessment through TikTok; and 3) a satisfaction survey for learning activities. The statistical methods employed for data analysis included frequency analysis, calculation of mean and standard deviation, as well as a T-test for dependent samples. The research revealed that students’ English-speaking skills, as assessed during the preparation course before their cooperative education program, were lower ( = 11.80, S.D. = 1.324) compared to their English-speaking skills after receiving instruction using the TikTok application (= 13.07, S.D. = 1.388). This difference reached a level of statistical significance at α = 0.05. Furthermore, the students reported a high level of overall satisfaction (= 4.41, S.D. = 0.601). These students perceive the video content as providing a straightforward duet that enables them to apply their English-speaking skills in real-life scenarios. This advantage fosters a sense of preparedness among students as they begin their cooperative education course.